1985
DOI: 10.1172/jci112027
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fab antibodies in humans. Predominance of minor immunoglobulin G subclasses in rheumatoid arthritis.

Abstract: Isoelectric focusing analyses of sera from patients with rheumatoid arthritis (RA) demonstrate two populations of antibodies directed aanst the Fab portion of pooled human IgG. One population is composed of polyclonal akline anti-Fab antibodies (aFABA) and the other, acidic aFABA which are more clonally restricted. In this study we have identified the immunoglobulin classes and subclasses of these antibodies in RA sera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…Without question, the most antigenic sites were those exposed in or adjacent to the lower hinge by proteases that generated F(abЈ) 2 s. It also became apparent that IgG3 was highly represented among the human anti-F(abЈ) 2 autoantibodies, similar to reports of IgG3 anti-Fab autoantibodies in two diseases (27,40). It is not clear what factors might bias anti-hinge autoantibodies toward IgG3.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Without question, the most antigenic sites were those exposed in or adjacent to the lower hinge by proteases that generated F(abЈ) 2 s. It also became apparent that IgG3 was highly represented among the human anti-F(abЈ) 2 autoantibodies, similar to reports of IgG3 anti-Fab autoantibodies in two diseases (27,40). It is not clear what factors might bias anti-hinge autoantibodies toward IgG3.…”
Section: Discussionmentioning
confidence: 90%
“…A functional role for anti-hinge autoantibodies remains uncertain although several investigations showed correlations between serum titers of the Abs and pathogical conditions such as systemic lupus erythematosus (38), cold agglutination (39), HIV (40), and rheumatoid arthritis (25). One group also suggested a potential immunoregulatory role for anti-hinge autoantibodies via induction of B cell apoptosis (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…66 Studies have correlated the titer of anti-hinge autoantibodies with pathological conditions such as cold agglutination, HIV, rheumatoid arthritis, and systemic lupus erythmatosus. [68][69][70][71] Others have suggested that natural anti-hinge autoantibodies bound to antigen-engaged F(ab') 2 fragments serve to augment complement activity. 72 One group speculated that anti-hinge autoantibodies can serve in an immunoregulatory role by inducing B cell apoptosis in antigen-engaged B cells by binding to the inhibitory receptor FcγRIIb.…”
Section: Autoantibodies Directed Against Cleaved Igg1 Hingementioning
confidence: 99%